A Systematic Review of the Mechanisms Involved in Immune Checkpoint Inhibitors Cardiotoxicity and Challenges to Improve Clinical Safety - Rubio-Infante, Nestor; Ramírez-Flores, Yoel Adbel; Castillo, Elena Cristina; Lozano, Omar; García-Rivas, Gerardo; Torre-Amione, Guillermo (Frontiers in Cell and Developmental Biology, 2022)
Immune checkpoint inhibitors (ICIs) are monoclonal antibodies that block CTLA-4, PD-1, or PD-L1 and induce the activation of the immune system against cancer. Despite the efficacy of ICIs, which has improved the oncotherapy for patients with a variety of malignancies, several immune-related adverse events (irAEs) have been described, including those affecting the heart. Cardiac irAEs after ICI therapies, including myocarditis, can become life-threatening, and their pathogenic mechanisms remain unclear. Here, a systematic analysis was performed regarding the potential immune mechanisms underlying cardiac irAEs based on the immune adverse events induced by the ICIs: 1) recruitment of CD4+ and CD8+ T cells, 2) autoantibody-mediated cardiotoxicity, and 3) inflammatory cytokines. Furthermore, the impact of dual therapies in ICI-induced cardiac irAEs and the potential risk factors are reviewed. We propose that self-antigens released from cardiac tissues or cancer cells and the severity/advancement of cancer disease have an important role in ICI cardiotoxicity.